Innovation in the State: Continuous Improvement with ITIL and Agile Methodologies in the Integrated Financial Information System [S.I.I.F.] - Ferraro, María de los Angeles (2025)
This work presents a case of modernization of the state in the province of Corrientes. In particular, it focused on the area of provincial public administration, General Accounting of the Province of Corrientes (CGCP) in the area of Information Technology (IT), Systems Directorate, where the administration of the Integrated Financial Information System (S.I.I.F) is carried out. The S.I.I.F is established by the Financial Administration and Control, Contracting and Administration of Public Sector Assets Act N ° 5,571, passed in July 2004 in the province of Corrientes. The general objective was to design an ITIL-based process model for software life cycle management, focusing on version control and requirement traceability and applying it in the IT area of the provincial public administration. The proposal was implemented through a tool designed to contribute to the traceability of software requirements and is complemented by other elements such as the Scrum Methodology, Kanban Tables, digital documentation and other computer tools. The challenge of implementing the model aims to produce a uniform, coordinated, registered and repeatable work scheme that allows changes to be managed in a managed and planned manner in an IT area, progressively generating a cycle of continuous improvement. The results demonstrate how IT innovation can drive efficiency and continuous improvement in public administration.